The Implementation of the Project-Based Learning Method to Enhance Student Engagement and Learning Independence in Islamic Education for Grade VII at SMP IT DOD Medan - Penara Nico (Yayasan Bayt Shufiya Nusantara, 2023)
This study aims to determine the effectiveness of the Project Based Learning (PJBL) model in increasing student activeness, independence, and learning outcomes in the subject of Islamic Religious Education (PAI) grade VIII at SMP IT DOD Medan. The method used is quantitative with a population of 120 students. The data collection technique was carried out through pre-test and post-test. Data analysis was conducted using SPSS with normality, homogeneity, and paired sample t-test. The results of the study show that PJBL is effective in increasing students' learning activity and independence. The calculated t value was greater than the t table (2,126 > 1,684), with a contribution to the improvement of learning outcomes by 32.6%.